Immunohistochemical approach to the pathogenesis of clinical cases of Bovine Herpesvirus type 5 infections - Cardoso Tereza C; Ferrari Heitor F; Garcia Andrea F; Bregano Livia C; Andrade Alexandre L; Nogueira Adriana HC (BMC, 2010)
Abstract Meningoencephalitis by Herpesvirus type 5 (BoHV-5) in cattle has some features that are similar to those of herpetic encephalitis in humans and other animal species. Human Herpesvirus 3 (commonly known as Varicella-zoster virus 1), herpes simplex viruses (HSV), and equid Herpesvirus 1 (EHV-1) induce an intense inflammatory, vascular and cellular response. In spite of the many reports describing the histological lesions associated with natural and experimental infections, the immunopathological mechanisms for the development of neurological disorder have not been established. A total of twenty calf brains were selected from the Veterinary School, University of São Paulo State, Araçatuba, Brazil, after confirmation of BoHV-5 infection by virus isolation as well as by a molecular approach. The first part of the study characterized the microscopic lesions associated with the brain areas in the central nervous system (CNS) that tested positive in a viral US9 gene hybridization assay. The frontal cortex (Fc), parietal cortex (Pc), thalamus (T) and mesencephalon (M) were studied. Secondly, distinct pathogenesis mechanisms that take place in acute cases were investigated by an immunohistochemistry assay. This study found the frontal cortex to be the main region where intense oxidative stress phenomena (AOP-1) and synaptic protein expression (SNAP-25) were closely related to inflammatory cuffs, satellitosis and gliosis, which represent the most frequently observed neurological lesions. Moreover, MMP-9 expression was shown to be localized in the leptomeninges, in the parenchyma and around mononuclear infiltrates (p < 0.0001). These data open a new perspective in understanding the role of the AOP-1, MMP-9 and SNAP-25 proteins in mediating BoHV-5 pathogenesis and the strategies of host-virus interaction in order to invade de CNS.